Infraestructura Verde Centrada en el Ser Humano: Potenciando la Seguridad Humana y el Bienestar en Entornos Urbanos - Trevisan, Simone (Revista Latinoamericana de Ambiente Construido y Sostenibilidad, 2024)
The research focuses on human security as an expanded concept, encompassing the protection of life and well-being in urban areas, which is relevant to the discussion on sustainable urban planning. The objective of this study is to show the importance of integrating green infrastructure with human security principles in cities, aiming to improve the quality of life and well-being of residents. Through an exploratory approach, the study combines a literature review, comparative analysis, and case studies, focusing on successful international examples of green infrastructure implementations. The findings suggest that green infrastructure not only contributes to environmental improvement but also promotes social cohesion and reduces inequalities, thereby increasing the resilience of cities to environmental and social crises. The study provides a theoretical foundation for the implementation of more inclusive and sustainable public policies, while also proposing the use of continuous monitoring technologies, such as applications, to evaluate and modify urban interventions. The social and environmental benefits include promoting residents’ mental and physical health, reducing pollution, and creating public spaces that foster community interaction and environmental preservation.